2021 Kazanjian Lecture: Caring for Children With Facial Anomalies—Inspiring the Next Generation. Issue 2 (June 2022) - Gosain, Arun K.; Gutowski, Kristof S.
Varaztad Kazanjian stood for innovation in plastic surgery, serving as a founder of many of the craniomaxillofacial principles practiced today. However, we have seen attrition in career interest toward craniofacial and pediatric plastic surgery as trainees progress from medical school to early career. We explore several aspects of our specialty that could help reinvigorate enthusiasm for our specialty and the retention of young surgeons. We begin by judging career success and defining the patient population we wish to serve. We examine several areas by which our specialty can be perceived as more attractive to young surgeons, to include early mentorship and maintaining these mentoring relationships beyond the training period. We emphasize the need to diversify our trainees and include them in efforts to expand innovation in our specialty. We discuss the need to champion craniofacial and pediatric plastic surgery as mission-critical to our institutions, involve trainees and young surgeons in advocacy efforts on behalf of our patients, and involve trainees and young surgeons in global health efforts. We discuss how to structure our divisions to make craniofacial and pediatric plastic surgery an inviting environment that welcomes new participants, rather than making them feel they are working their way through an "old boys' club." Innovation alone will not sustain our specialty unless we mentor the next generation to want to continue in the line of innovation that drew us to this specialty.